Implementing Technology in English Language Learning: Friend or Foe - Puspitasari, Maya; Juhana; Pelawi, Muhammad Arifin (Indonesian Research Journal in Education |IRJE|, 2023)
Nowadays, foreign language education relies heavily on digital technology. A growing emphasis on 21st-century skills and massive technological advancements raise more concerns than ever about the competency of English as Foreign Language (EFL) teachers. This study aimed to investigate the level of digital technology readiness among EFL teachers in Indonesia and respondents’ experiences in implementing technology in the education curriculum in Indonesian schools. A quantitative survey of 90 teachers was conducted to observe the teachers’ perceptions and experiences with technology. The study showed that technological advancement has helped teachers teach the English language. The respondents believed that technology could improve the students’ English skills, including speaking, listening, reading, writing, pronunciation, and grammar. This study provided the teachers' perception of the value of using technology in English language learning.